Distributed Attitude Consensus for Multiple Rigid Spacecraft under Jointly Connected Switching Topologies - Long Ma; Shicheng Wang; Haibo Min; Shouyi Liao; Zhiguo Liu (Journal of Control Science and Engineering)
We study the distributed leader-following attitude consensus problem for multiple rigid spacecraft with a single leader under jointly connected switching topologies. Two cases are considered, where the first case is with a static leader and the second case is with a dynamic leader. By constructing an auxiliary vector and a distributed observer for each follower spacecraft, the controllers are designed to drive all the attitudes of the follower spacecraft to the leader’s, respectively, for both of the two cases, though there are some time intervals in which the communication topology is not connected. The whole system is proved to be stable by using common Lyapunov function method. Finally, the theoretical result is illustrated by numerical simulations.